Modelagem hidrológica da bacia do rio Jucu utilizando o modelo DHSVM - Oliveira, Kenny Delmonte (2014)
The aim of this study was to hydrological modeling of river basin Jucu using the dynamic physical model and distributed DHSVM (Distributed Hydrology Soil Vegetation Model), which explicitly represents the integrated processes of hydrological phenomena. The first stage of the work consisted in the carefully collect data model input, both through literature review and by using geotechnology. The second step consisted in hydrological modeling. Climate, vegetation and soil variables were used for model calibration, validation and to simulate the flow on a daily time step at Fazenda Jucuruaba station, main river gaging station Jucu. Following the same procedure it was validate the flow in the upstream station Córrego do Galo, in order to understand the effect of calibration on watercourses located on upstream section. This analysis yielded simulations that met a high accuracy prediction, with moderate demand expenditure of time and technical efforts for calibration, obtaining Nash and Sutcliffe coefficient of 0.86, adjusted Nash and Sutcliffe coefficient of 0.60 , percent bias of -1.55 and the standard deviation of measured data of 0.39. The DHSVM showed satisfactory performance, showing potential to be applied in different regions than those for which it was developed and tested.